Kecerdasan Manusia Menurut Al-Qur’an: Literatur riview - Shafaunnida, Arzi; Muhid, Abdul (Jurnal Pendidikan Islam, 2022)
Intellectual Intelligence in the Qur'an which has been possessed by humans since humans were born with the gift of intelligence privileges and understands and learns about terms related to intelligence. Emotional feelings that are owned and felt by humans described in the Qur'an such as love, anger, fear, joy and sadness will always be expressed and cannot be separated about ta'qilun (reason) because intelligent human characteristics will always use his mind to always Yatafakkarun (think) in order to achieve truth and goodness. In addition, intelligent humans will always think and reflect on their life which continues to Yatadabbarun (revolving). Humans will gain (Yatafaqqahun) and always understand every knowledge that will be obtained and always optimize the potentials of a worldly nature because intelligent humans will always remember their God and always do dhikr (yatadzakkarun) and pray.